The IIUM low speed wind tunnel - Hasim, Fadilah; Rusyadi, Rusman; Surya, Wijaya Indra; , Fariduzzaman; Asrar, Waqar; Omar, Ashraf Ali; Syed Mohamed Ali, Jaffar; Aminanda, Yulfian; Kafafy, Raed (2008)
The new IIUM low speed tunnel is of a closed-loop type having a test section of 1.5m × 2.3m × 6m and a maximum speed of 50 m/s. This paper describes measurement results for initial calibration and flow characteristics of this newly constructed wind tunnel. The results show that the total pressure varies within 0.999≤Cpt≤1.003, the dynamic pressure varies from -0.5 to 0.4 percent from the plane mean value, the flow angularity holds within ±0.2º and the boundary layer thickness is less than 2 percent of the equivalent hydraulic diameter of the test section.